Stellar populations and ionised gas in central spheroidal galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Lorenzoni, Vanessa; Rembold, Sandro B.
Abstract : We investigate the stellar populations and ionised gas properties of a sample of central spheroidal galaxies in order to better constrain their history of star formation and gas excitation mechanism. We select galaxies from Spheroids Panchromatic Investigation in Different Environmental Regions (SPIDER) catalogue and separate these galaxies in different regimes of halo and galaxy mass. To characterise the stellar population properties of these galaxies we use the stellar population synthesis method with the Starlight code, and the presence of ionised gas is identified by measurements of the Hα equivalent width. We analyse how these properties behave as a function of the galaxy stellar mass and the parent halo mass. A trend is observed in the sense of increased ionised gas emission for low-mass centrals in high-mass halos. We interpret this trend in a scenario of intracluster medium (ICM) cooling versus active galactic nuclei (AGN) feedback in a Bondi accretion context.